STRATEGI PENGUATAN SUMBER DAYA MANUSIA (SDM) DI HINTERLAND UNTUK MENDUKUNG EFISIENSI INFRASTRUKTUR PELABUHAN DALAM PERSPEKTIF PEMBANGUNAN BERKELANJUTAN - Desy Yulia Aryani; Suherman Suherman; Renny Hermawati; Kurniawan Teguh Santoso (UNIMAR AMNI Semarang, 2026)
This article aims to analyze the strategy of strengthening Human Resources (HR) in the hinterland area in order to improve the efficiency of port infrastructure, especially Tanjung Emas Port, in the perspective of sustainable development. The purpose of this research is to explain the quality, development, accessibility of hinterland and the effectiveness of the Human Resources (HR) logistics system in influencing the efficiency of port infrastructure. The focus of the research is directed at 3 (three) main variables, namely the quality of Human Resources (HR), the development of Human Resources (HR), and the accessibility of hinterland, with the effectiveness of logistics systems as intervening variables and port infrastructure efficiency as dependent variables. This study uses a quantitative approach with data collection techniques through questionnaires on 127 respondents who were selected using simple random sampling techniques. The data were analyzed using multiple linear regression. The results of the study show that all independent variables, namely the quality of Human Resources (HR), Human Resources (HR) development, and hinterland accessibility, have a significant effect on the effectiveness of the logistics system and the efficiency of port infrastructure. The effectiveness of logistics systems has also been proven to have a significant influence on the efficiency of port infrastructure, as well as being a strong mediating variable. These findings confirm the importance of integration between strengthening the capacity of hinterland Human Resources (HR) and logistics system management in an effort to improve port performance in a sustainable manner.